Oral health in individuals with psychotic disorders - Jovanović Svetlana; Gajić Ivanka (Serbian Medical Society - Dental Section, Belgrade, 2008)
Mental disorders are an important problem in every national health care service. The importance of psychotic disorders is not only their frequency but also their long-term character, recurrence, association with other diseases, costs and consequences for the family and society. Psychotic disorders (schizophrenia, schizoaffective disorder, bipolar disorders and depression) and their treatment may result in serious oral diseases. These disorders and medications used to treat them may lead to a series of oral complications and side effects, predominantly high prevalence of carious and extracted teeth, periodontal disease, inadequate oral hygiene, xerostomia, burning mouth syndrome, bad breath and gustatory sense dysfunction. Psychotic disorders affect oral and dental health in two ways. Behavioural changes affect the oral hygiene maintenance and lead to bad habits and attitudes towards oral health. Antipsychotic therapy has adverse effects on oral health. Literature data suggest that oral health in patients with psychotic disorders is poor and highlight the need to develop specific preventive programmes, which would be aimed at improving behaviour of this population at risk in the oral health care system.